Biodiesel production from Jatropha oil by supercritical methanol - Samniang, Amonrat; Kajorncheappan-ngarm, Somjai (Engineering and Applied Science Research, 2014)
The objective of this research was to study the biodiesel production from crude Jatropha oil by using methanol. The study was focused on the effect of the molar ratio of methanol to oil (20:1-50:1), temperature (250-350°C), pressure (8-17 MPa) and reaction time (5-15 min) on methyl ester yield from transesterification reaction. It was found that the highest methyl ester yield of 84.6 was obtained at the condition of temperature 320°C, pressure 17 MPa, a molar ratio of methanol to oil 40:1 and reaction time 5 min. All the properties of biodiesel from Jatropha oil were improved comparing to those of starting crude oils. Most of the properties such as acid value, iodine value, viscosity and heating value of the biodiesel from Jatropha oil met the biodiesel standard.